c = 3 写下一个python语句,计算z的值,由下式定义: z =(2a-3b)/ 8 +(42 /(a ^ 2 - b ^ 2))x(( 2 / a)+(c / 6))/ b) 提交Python表达式和键入时获得的值print(z) >>> a = 5 >>> b = 2 >>> c = 3 >>> z =((2 * a - 3 * b)/ 8)+((42 /(a ** 2 - b ** 2))*(((2 / a)+(c / 6))/ b)Type the following commands into a Python Shella = 5b = 2c = 3Write down a python statement that would compute the value of z which is defined by the following equation:z = (2a-3b)/8 + (42/(a^2 - b^2)) x ((2/a)+(c/6))/b)Submit the Python expression and the value you get when you type print(z)>>> a = 5>>> b = 2>>> c = 3>>> z = ((2 * a - 3* b)/8) + ((42 / (a**2 - b**2)) * (((2/a)+(c/6))/b)推荐答案亲爱的会员, 表达式中缺少一个括号。 以下是正确的表达方式: - z =((2 * a - 3 * b)/ 8)+( 42 /(a ** 2 - b ** 2))*(((2 / a)+(c / 6))/ b) 您最近可以查看我发布的以下文章。您的反馈和评价非常感谢。 PHP应用程序 问候, SunilDear Member,There is a missing parenthesis in your expression.Following is the correct expression:-z = ((2 * a - 3* b)/8) + (42 / (a**2 - b**2)) * (((2/a)+(c/6))/b)You may please go through following article posted by me recently. Your feedback and rating is highly appreciated.Chat Application in PHPwith regards,Sunil 这篇关于Python代码错误语法错误的文章就介绍到这了,希望我们推荐的答案对大家有所帮助,也希望大家多多支持! 上岸,阿里云!